Critical Factors in the Performance and Cost of Two-Dimensional Gene Scanning: RB1 as a Model. (October 1998) - Dhanda, R.K.; Orsouw, N.J. van; Sigalas, I.; Eng, C.; Vijg, J.
Two-dimensional (2-D) gene scanning (TDGS) is a method for mutation detection based on the electrophoretic separation of PCR-amplified DNA fragments according to size and base pair sequence. The use of denaturing gradient gel electrophoresis (DGGE) as the second separation step provides virtually 100% sensitivity, while the 2-D format allows the inspection of multiple gene fragments simultaneously. Analysis of many exons in parallel is greatly facilitated by extensive PCR multiplexing based on preamplification by long-distance PCR. Recently, TDGS has been applied to detect mutations in the retinoblastoma tumor suppressor gene RB1 . Using RB1 as a model, we have now analyzed each step of the protocol, presenting overall improvements and a detailed cost analysis, where the total cost of the assay is found to be about $40 (US). An overall picture of TDGS cost-performance, as compared to direct sequencing, is provided as a function of the number of target fragments.